2019
DOI: 10.20900/jpbs.20190013
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Clinical Sex Differences in Antipsychotic-Induced Metabolic Disturbances: A Narrative Review of Adiposity and Glucose Metabolism

Abstract: Antipsychotic (AP) medications are associated with an increased risk of developing metabolic side effects including weight gain, type 2 diabetes (T2D), dyslipidemia, and hypertension. In the majority of clinical studies, females on APs are noted to gain more weight, and are more likely to be diagnosed with metabolic syndrome when compared to males. However, the data is less clear when comparing sex disparities associated with other specific AP-induced metabolic risk factors. Accumulating evidence has demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 138 publications
(253 reference statements)
1
14
0
Order By: Relevance
“…In a recent review, Castellani et al (48) found that the majority of clinical studies indicated that women on AP gained more weight than men, and were more at risk for metabolic syndrome. The pathway to metabolic side-effects induced especially by second generation AP remains incompletely understood.…”
Section: Metabolic Effectsmentioning
confidence: 99%
“…In a recent review, Castellani et al (48) found that the majority of clinical studies indicated that women on AP gained more weight than men, and were more at risk for metabolic syndrome. The pathway to metabolic side-effects induced especially by second generation AP remains incompletely understood.…”
Section: Metabolic Effectsmentioning
confidence: 99%
“…Female sex has also been related to more extensive weight gain following antipsychotic drug treatment (17), whereas male sex has been linked to lower HDL-C and higher triglyceride (TG) levels following drug treatment (18,19). One proposed mechanism underlying these sex differences in metabolic co-morbidities is the influence of sex hormones on regulating food intake, energy expenditure, and drug metabolism (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Research with a larger population is needed to see the effect and mechanism of increasing body weight on gender. 14 This study has several limitations. First, the influence of independent variables (such as patients' demographic data and nutritional intake of patients before therapy) towards weight gain cannot be analyzed since this study was conducted retrospectively.…”
Section: Discussionmentioning
confidence: 92%